Creativity in planning: a fuzzy concept? - Kunzmann, Klaus R. (TH Zürich, ORL-Institut, 2005)
Kreativität lautet landauf landab die Antwort der Kommunen und Regionen auf die Herausforderungen des technologischen und Strukturwandels. Sie ist der Königsweg zur Herstellung von Wettbewerbsfähigkeit und zur Selbstqualifizierung als guter Standort für die neue Klasse der Kreativen. Die Kreativwirtschaft wird als der Motor der künftigen Wirtschaftsentwicklung betrachtet, als die Branche, die die von der alten Industrie verlassenen Brachen wieder belebt. Kein Wunder, dass in der Kommunal- und Regionalpolitik Kreativität das Schlagwort der Stunde ist. Ohne den Anspruch auf eine abschließende Begriffsklärung in einem sich wandelnden Milieu will der Beitrag zu einem kreativen Denken und Handeln in den raumbezogenen Planungen ermuntern. oc/difu

In recent years, all around the world, Europe, America, Asia, creativity has become a buzz word in urban and regional policy. Cities and regions have to be "creative" in order to cope with the challenges of technological and structural change, to be competitive or to qualify as locations for the new creative class. Creative industries are considered the engine for future economic development and the salvation for run-down inner city quarters, brownfields or first-generation suburbs. Business consultants earn their fees by stressing creativity as the most essential condition for the success of innovative businesses. Hence, it is not surprising that "creativity" has become a much used term in urban and regional policies. The essay presents findings on creativity without the ambition to bring clarity into a concept, which is open for further interpretation. It is rather an invitation to creative thinking and action in planning. difu
Keywords: Stadtentwicklungsplanung; Strukturwandel; Innovation; Industrie; Wirtschaftsentwicklung; Regionalplanung; Planungstheorie; Kulturwirtschaft; Kreativität; Planungsprozess; Kreativwirtschaft